Work Experience (Money Management and Social Involvement). Course Outline 8769. (Distributed by ERIC Clearinghouse, 1971)
A course was designed to help students develop traits which have worthwhile carry-over values which will prove useful in the continuation or completion of their formal education. The proper methods used in wise money management, covering those areas of earnings, savings, spending, budgeting and calculations of deductions are discussed and practiced in some depth during the course. Work-experience students learn self motivational concepts, which will aid them in seeking further technical education. This report is an outline developed through the cooperative efforts of the instructive and administrative personnel. The course is divided into three sections: (1) money management; (2) the future and you, and (3) a post-test. A list of ten goals are presented which the work-experience student should be able to demonstrate upon completion of the program. Among these are to obtain knowledge of the procedures involved in securing employment, and the generally accepted procedures in preparing for a job interview. (Author/BW)